EXPLORING THE IMPACT OF SOCIAL MEDIA ON SELF-ESTEEM AMONG ADOLESCENTS - Aatikah Noor; Dr. Sumera Mehmood; Nudrat Fatima (International Journal of Contemporary Issues in Social Sciences, 2024)
This qualitative research explores the far-reaching relationship between social media involvement and adolescent self-esteem. The study looks at the differing encounters that young people have with a range of social media, examining concepts such as social comparison and validation-seeking behavior; strategic highlighting of oneself, and platform-specific impact. Interviews and focus group discussions suggest that the pressure to conform creeps in daily, leaving most people feeling they live up to expectations not out of merit but only because they are unfamiliar with alternative paths. Their impact was dual-edged: they provided prompt hits to self-esteem, but fueled dependencies on outside validation. In addition, the study revealed differences between virtual selves and real-life encounters. The experience of each platform was seen as different by category: Instagram, Snapchat and TikTok. Although the study points out problems with social media, it also shows that strong offline networks and media literacy can serve as protective roles. The findings highlight the great urgency of intervention that is appropriately targeted to encourage critical media literacy, authentic self-expression and strong offline networks in order to reduce the harm created by social media, promote teen well-being in this digital era.